Filtering the NMR Spectra of Complex Mixtures through Polymer‐Mediated Paramagnetic Spin Relaxation. Issue 72 (21st November 2018) - Correa, Juan; Pinto, Luiz F.; Zhao, Libo; Riguera, Ricardo; Fernandez‐Megia, Eduardo
Abstract: A polymer‐mediated paramagnetic spin relaxation (PSR) filter is presented for the selective suppression of signals from polymer‐interacting species in the 1D and 2D NMR spectra of mixtures. The combined use of Gd 3+ and a polymer with a high transverse relaxation enhancement ( R 2p, which gives a measure of the Gd 3+ ‐complexing ability) results in the suppression of signals from any polymer‐interacting component in mixtures, irrespective of their R 2p . By using poly(acrylic acid) (PAA) as a model system, we demonstrate selective filtering of the signals of typical low‐ R 2p species (insensitive to Gd 3+ ), such as molecular/polymeric cations and non‐ionic polymers, which, through PAA recognition (electrostatic/hydrogen‐bonding interactions), become exposed to the paramagnetic effect of Gd 3+, while leaving non‐PAA‐interacting species unaffected. Typical suppression conditions involve PAA (approximately equimolar amount with respect to the species to be filtered) accompanied by sub‐mm concentrations of Gd 3+ and T 2 ‐filters ≤100 ms. Overall, by exploiting the PSR principles and the recognition properties of polymers, selective NMR filtrations that are not attainable by diffusion, relaxation, or direct PSR filters, can be achieved. Abstract : NMR spectral filtering : A polymer‐mediated paramagnetic spin relaxation filter has been devised for selective suppression of the signals of polymer‐interacting species in the 1D and 2D NMR spectra of mixtures (see graphic).